Optimalisasi Anggaran Biaya Proyek Pembangunan Villa Grand Sinensis Menggunakan Metode Value Engineering - Koilmo, Markus; Yakin, Kusnul; Octaviani, Maulidya (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2019)
Along with the time, the rise of development in various cities in Indonesia is also increasing. This phenomenon leads to the increase of development demands in all fields, especially in developing cities. One specific place in Malang City that is under the elite settlements construction is the one that located in Tegal Rejo Street 22, Ketindang, Lawang. Based on the previous description, it is very important to implement value engineering in the construction project of Grand Sinensis Villa which is expected to bring alternatives to replace old work items as recommendations for the relevant parties, which provides benefits in the form of cost savings. In the process of budget analysis using the value engineering method, there are 4 stages that will be analyzed, namely: Information Phase, Creative Phase, Analysis Phase and Recommendation Phase. From the results of analysis using Value Engineering method, there are obtained several alternatives that can be proposed, namely: work of concrete items using floordeck with cost savings of: 30,910,797 rupiahs and the installation of water heather using GAS with cost savings of 3.230.000 rupiahs.